Effect of work discipline, work environment and work motivation on employee performance at PT. Autostar Mandiri Technotama - Filberto Salim; Yovie Ernanda; Yenny; Wulansari (Institute of Computer Science (IOCS), 2023)
The purpose of this research is to examine and analyze the influence of work discipline, work environment, and work motivation on the performance of employees at PT. Autostar Mandiri Technotama. This research is descriptive research. The population and sample of this research are employees of PT. Autostar Mandiri Teknotama numbered 67 people, with a saturated sampling technique. The statistical method used is multiple linear regression analysis. The results showed that partially stated work discipline, work environment, and work motivation had a significant effect on employee performance at PT Autostar Mandiri Teknotama. And Simultaneously states that all independent variables have a significant effect on the performance of employees at PT. Teknotama independent autostar.